Hydrophilic carbon fiber spinning solution and airflow spinning method thereof

By introducing liquid melamine phosphate and air-flow spinning methods, carbon nanofibers with excellent hydrophilic properties are prepared, which solves the problem of strong hydrophobicity of traditional carbon fibers and realizes efficient application of materials in the fields of catalysis, energy, water treatment, etc.

CN119507069AActive Publication Date: 2025-02-25WUHAN TEXTILE UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411749846.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-25
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Traditional carbon fibers have strong hydrophobicity on the surface and are difficult to meet the needs of catalysis, energy, water treatment and other fields, which limits the development of carbon fiber materials.

Method used

The spinning liquid is prepared by introducing liquid melamine phosphate, and the hydrophilic carbon fiber spinning raw liquid is prepared by air flow spinning method, and the fibers are maintained in the process of high-temperature carbonization.

Benefits of technology

It realizes efficient preparation of hydrophilic carbon nanofibers, with dense fiber structure and good hydrophilic properties on the surface without additional treatment, which has high application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507069A_ABST
    Figure CN119507069A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of carbon fiber preparation, and relates to a hydrophilic carbon fiber spinning stock solution and an airflow spinning method thereof, precursor spinning raw materials are added into N-N-dimethylformamide, then liquid melamine phosphate is introduced for modification, and the hydrophilic carbon fiber spinning stock solution is prepared. Transferring the hydrophilic carbon fiber spinning solution into an injection pump, and performing solution blowing spinning under specific spinning parameters to obtain precursor fiber cotton; and drying the precursor fiber cotton, and carbonizing to obtain the hydrophilic carbon nanofiber. The liquid melamine phosphate is introduced to prepare the spinning solution, the viscosity of the spinning solution is effectively reduced, the stability of the spinning solution is improved, the spinning efficiency and the fiber quality are improved, the spinning solution is subjected to solution blowing spinning and carbonization, and the prepared hydrophilic carbon nanofiber is compact in structure and high in hydrophilicity. The excellent hydrophilic capacity can still be kept without surface treatment, large-scale production can be carried out, and extremely high application value is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon fiber preparation, and in particular relates to a hydrophilic carbon fiber spinning solution and an air-spinning method thereof. Background Art

[0002] Carbon fiber has been widely used in many fields such as aerospace, automobile manufacturing and sporting goods due to its high modulus, high tensile strength, corrosion resistance, good acid and alkali resistance and excellent mechanical properties. However, the surface of traditional carbon nanofibers has strong hydrophobic properties, which limits its actual effect and efficiency in many potential applications. The large-scale preparation of hydrophilic carbon fibers is of great value. As filter materials and electrode materials, hydrophilic carbon fibers show excellent adsorption capacity and conductivity. This unique hydrophilic property significantly enhances the application value of the material in water treatment, energy storage and biomedicine. In addition, hydrophilic carbon fibers can significantly improve the interfacial bonding force in composite materials, thereby enhancing the overall mechanical properties of the material.

[0003] The preparation methods of hydrophilic carbon fibers mostly use plasma modification, plasma treatment, surface coating, high-temperature treatment, etc. The main principle is to use modified materials to perform surface modification on non-hydrophilic carbon fibers. However, the above-mentioned modification technologies are mostly suitable for carbon fiber surface treatment, and a two-step strategy of spinning plus post-treatment is adopted. However, the prepared carbon fiber materials have poor hydrophilicity. With the development of catalysis, energy, water treatment and other fields, the hydrophilic carbon fiber materials prepared by traditional surface treatment technologies can no longer meet industry needs, which greatly limits the development of carbon fiber materials. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a hydrophilic carbon fiber spinning solution and an air-spinning method thereof. The spinning solution is prepared by introducing liquid melamine phosphate, and the hydrophilic carbon nanofibers prepared after spraying and high-temperature carbonization can maintain excellent hydrophilicity without surface treatment.

[0005] The present invention is achieved through the following technical solutions:

[0006] The first aspect of the present invention provides a hydrophilic carbon fiber spinning solution, wherein the hydrophilic carbon fiber spinning solution is prepared by adding a precursor spinning raw material to NN-dimethylformamide (DMF), and then introducing liquid melamine phosphate for modification, wherein the mass ratio of the precursor spinning raw material, liquid melamine phosphate, and NN-dimethylformamide is 10-20:3-6:90-110. The preparation method of the liquid melamine phosphate is as follows: modifying auxiliary phosphoric acid in liquid melamine resin, stirring with a magnetic stirrer for 2 hours to mix evenly to prepare liquid melamine phosphate, wherein the mass ratio of the liquid melamine resin to the modified auxiliary phosphoric acid is 1:3-6.

[0007] Furthermore, the precursor spinning raw material is one or both of polyacrylonitrile and lignin.

[0008] The second aspect of the present invention provides a method for air-spinning the hydrophilic carbon fiber spinning solution, comprising the following steps:

[0009] (1) transferring the hydrophilic carbon fiber spinning stock solution into a syringe pump to perform solution spray spinning to obtain precursor fiber cotton;

[0010] (2) After the precursor fiber cotton is dried, it is carbonized at 400-800° C. in a nitrogen environment to obtain hydrophilic carbon nanofibers.

[0011] Furthermore, in the solution jet spinning process, the spinning parameters are set as follows: the spinning air pressure is 0.2-0.4 MPa, the spinning flow rate is stable at 10-30 mL / h, and the spinning distance is 30 cm.

[0012] Furthermore, the drying is specifically as follows: placing the precursor fiber in a drying oven at 50-60°C for 10-20 hours of drying. The main purpose of this process is to remove residual solvent and moisture in the fiber to ensure the structural stability and performance consistency of the fiber. Long-term drying can effectively reduce the moisture content in the fiber, avoiding fiber deformation, performance degradation or other adverse effects caused by residual moisture during subsequent processing.

[0013] Furthermore, the dried precursor fiber cotton is placed in a muffle furnace for pre-oxidation at 220-260°C, and then carbonized. The purpose of pre-oxidation: In the air, the fiber surface reacts with oxygen to form oxygen-containing functional groups (such as carboxyl, alcohol, aldehyde, etc.). The formation of these functional groups helps to improve the structural stability of the fiber during the subsequent carbonization process, and reduces the volume shrinkage and fiber breakage during high-temperature carbonization, greatly enhancing the mechanical properties of the carbon nanofibers.

[0014] Furthermore, the heating rate of the carbonization is 4-8°C / min, and the carbonization time is 0.5-2h. The main purpose of this high temperature treatment step is to perform carbonization or sintering to obtain carbon nanofibers with good hydrophilic properties. The carbonization temperature is lower than 400°C, and the carbonization degree is low, resulting in poor mechanical properties of the prepared hydrophilic carbon nanofibers. Above 800°C, graphitization increases and hydrophilicity decreases. Carbonization between 400 and 800°C can ensure that the carbon nanofibers have good hydrophilicity.

[0015] The third aspect of the present invention provides a method for preparing hydrophilic carbon nanofibers, wherein the above-mentioned hydrophilic carbon fiber spinning stock solution is transferred into an injection pump, and solution spray spinning is performed to obtain precursor fiber cotton. After the precursor fiber cotton is dried, it is pre-oxidized at 220 to 260°C, and then carbonized at 400 to 800°C in a nitrogen environment to obtain hydrophilic carbon nanofibers.

[0016] A fourth aspect of the present invention provides hydrophilic carbon nanofibers prepared by the method described above.

[0017] The present application proposes to prepare a liquid melamine phosphate soluble in DMF by using liquid melamine resin as a matrix and adding phosphoric acid as a modification aid. Compared with commercial melamine materials, it can effectively avoid the common nano-melamine powder causing the viscosity of the spinning solution to increase after being added to the solution, thereby making the spinning process difficult. The liquid melamine phosphate of the present application has a better solubility in the DMF solvent, which effectively reduces the viscosity of the spinning solution. One point in particular is that when the liquid melamine phosphate is introduced into the PAN / DMF precursor spinning solution and the lignin / PAN / DMF precursor spinning solution, the formaldehyde group in the melamine phosphate will combine with the side chain of phosphoric acid to form a hydrophilic group. The formation of this hydrophilic group not only improves the stability of the spinning solution, but also significantly improves the spinning efficiency and fiber quality. Through solution spray spinning technology combined with a 400-800°C carbonization process, large-scale and efficient preparation of hydrophilic carbon nanofibers can be achieved. Melamine phosphate itself can be carbonized to form carbon fiber materials. During the calcination process, it synergistically enhances the density of hydrophilic carbon nanofibers with polyacrylonitrile and lignin, thereby improving its hydrophilic properties.

[0018] The advantages and positive effects of the present invention are:

[0019] (1) The present invention introduces liquid melamine phosphate into the spinning solution, which effectively reduces the viscosity of the spinning solution, improves the stability of the spinning solution, and improves the spinning efficiency and fiber quality.

[0020] (2) The air-jet spinning method of the present invention performs solution blowing spinning and carbonization on the spinning solution to prepare hydrophilic carbon nanofibers with dense structure. The fiber surface can still maintain excellent hydrophilicity without treatment, and has extremely high application value.

[0021] (3) The preparation method of the hydrophilic carbon fiber of the present invention is simple, low-cost, and can be produced on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a SEM image of the carbon nanofiber prepared in Example 1;

[0023] Figure 2 This is a macroscopic photograph of the carbon nanofiber prepared in Example 1;

[0024] Figure 3 This is a SEM image of the carbon nanofibers prepared in Example 2;

[0025] Figure 4 This is a macroscopic photograph of the carbon nanofiber prepared in Example 2;

[0026] Figure 5 This is a diagram of the water absorption process of the carbon nanofiber prepared in Example 1 (the water is dyed with a fluorescent agent);

[0027] Figure 6 This is a diagram of the water absorption process of the carbon nanofiber prepared in Example 2 (the water is dyed with a fluorescent agent);

[0028] Figure 7 This is the SEM image of the carbon nanofiber prepared in Comparative Example 1;

[0029] Figure 8 The hydrophobicity diagram of PAN-based carbon nanofibers prepared in Comparative Example 1;

[0030] Fig. 9 This is a SEM photo of the carbon nanofiber prepared in Comparative Example 2;

[0031] Fig.10 This is the SEM image of the carbon nanofiber prepared in Comparative Example 3;

[0032] Fig.11 The water contact angle of the PAN / melamine hydrophilic carbon nanofibers prepared with liquid melamine phosphate in Example 1 after carbonization at 800 degrees in a nitrogen atmosphere for 1 hour;

[0033] Fig.12 The water contact angle of the PAN / melamine hydrophilic carbon nanofibers prepared with liquid melamine phosphate in Example 3 after carbonization at 400 degrees in a nitrogen atmosphere for 1 hour;

[0034] Fig.13The water contact angle of PAN / melamine hydrophilic carbon nanofibers prepared with liquid melamine phosphate in Comparative Example 3 after carbonization at 1200 degrees in a nitrogen atmosphere for 1 hour;

[0035] Fig.14 The water contact angle of the lignin / PAN / melamine hydrophilic carbon nanofibers prepared with liquid melamine phosphate in Example 2 after carbonization at 800 degrees in a nitrogen atmosphere for 1 hour;

[0036] Fig.15 The water contact angle of the lignin / PAN / melamine hydrophilic carbon nanofibers prepared with liquid melamine phosphate in Example 4 after carbonization at 400 degrees in a nitrogen atmosphere for 1 hour;

[0037] Fig.16 This is the water contact angle of the lignin / PAN / melamine hydrophilic carbon nanofibers prepared with liquid melamine phosphate in Comparative Example 4 after carbonization at 1200 degrees in a nitrogen atmosphere for 1 hour. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0039] Example 1

[0040] A method for air-spinning a hydrophilic carbon fiber spinning solution comprises the following steps:

[0041] (1) Preparation of liquid melamine phosphate: 10 g of liquid melamine resin and 50 g of phosphoric acid as a modification aid were mixed with a magnetic stirrer for 2 h to prepare a uniformly mixed liquid melamine phosphate.

[0042] (2) Weigh 10 g of polyacrylonitrile, 5 g of liquid melamine phosphate, and 100 g of NN-dimethylformamide, stir with a magnetic stirrer for 2 hours, and prepare a hydrophilic carbon fiber spinning solution with good spinning viscosity after mixing evenly;

[0043] (3) The hydrophilic carbon fiber spinning solution was transferred into the injection pump, and the precursor fiber cotton was prepared by the solution jet spinning method. The spinning parameters were set as follows: the spinning pressure was 0.2 MPa, the spinning rate was 10 mL / h, and the spinning distance was 30 cm.

[0044] (4) After drying, the prepared precursor fiber cotton was placed in a tubular furnace and carbonized at 800°C in a nitrogen environment. The carbonization heating rate was 5°C / min and the holding time was 1h, and finally carbon nanofibers with good hydrophilic properties were obtained.

[0045] The SEM image of the carbon nanofiber prepared in Example 1 is as follows: Figure 1 As shown in the macroscopic photograph Figure 2 As shown, the water absorption process is as follows Figure 5 shown.

[0046] Example 2

[0047] The difference from Example 1 is that step (2) is: weigh 15 g of lignin, 5 g of polyacrylonitrile, 5 g of liquid melamine phosphate, and 100 g of NN-dimethylformamide, stir with a magnetic stirrer for 2 hours, and mix well to prepare a hydrophilic carbon fiber spinning solution with good spinning viscosity;

[0048] The SEM image of the carbon nanofibers prepared in Example 2 is as follows: Figure 3 As shown in the macroscopic photograph Figure 4 As shown, the water absorption process is as follows Figure 6 shown.

[0049] Example 3

[0050] The only difference from Example 1 is that the carbonization temperature is 400°C.

[0051] Example 4

[0052] The only difference from Example 2 is that the carbonization temperature is 400°C.

[0053] Comparative Example 1

[0054] The difference from Example 1 is that step (1) is omitted and liquid melamine phosphate is not added in step (2).

[0055] The SEM image of PAN-based carbon nanofibers prepared in Comparative Example 1 is as follows: Figure 7 As shown, the hydrophobic map is Figure 8 shown.

[0056] Comparative Example 2

[0057] The difference from Example 1 is steps (1) and (2):

[0058] (1) Weigh 10 g of powdered melamine and 50 g of DMF and stir with a magnetic stirrer for 2 h to prepare a uniformly mixed melamine solution.

[0059] (2) Weigh 10 g of polyacrylonitrile, 5 g of melamine solution, and 100 g of NN-dimethylformamide, stir with a magnetic stirrer for 2 hours, and prepare a hydrophilic carbon fiber spinning solution after mixing evenly.

[0060] The SEM photo of the carbon nanofiber prepared in Comparative Example 2 is as follows: Fig. 9 shown.

[0061] Comparative Example 3

[0062] The difference from Example 2 is steps (1) and (2).

[0063] (1) Weigh 10 g of powdered melamine and 50 g of DMF and stir with a magnetic stirrer for 2 h to prepare a uniformly mixed melamine solution.

[0064] (2) Weigh 15 g of lignin, 5 g of polyacrylonitrile, 5 g of melamine solution, and 100 g of NN-dimethylformamide, stir with a magnetic stirrer for 2 hours, and mix well to prepare a hydrophilic carbon fiber spinning solution;

[0065] The SEM photo of the carbon nanofiber prepared in Comparative Example 3 is as follows: Fig.10 shown.

[0066] Comparative Example 3

[0067] The only difference from Example 1 is that the carbonization temperature is 1200°C.

[0068] Comparative Example 4

[0069] The only difference from Example 2 is that the carbonization temperature is 1200°C.

[0070] Performance and testing

[0071] The carbon nanofibers prepared in Example 1, Example 2, and Comparative Examples 1 to 3 were subjected to electron microscope scanning. The SEM image of the carbon nanofibers prepared in Example 1 is as follows: Figure 1 The SEM image of the carbon nanofibers prepared in Example 2 is shown as Figure 3 As shown; the SEM image of the carbon nanofiber prepared in Comparative Example 1 is as shown Figure 7 As shown; the SEM image of the carbon nanofiber prepared in Comparative Example 2 is as shown Fig. 9 As shown; the SEM image of the carbon nanofiber prepared in Comparative Example 3 is as shown Fig.10 shown; contrast Figure 1 and Fig. 9 , Figure 3 and Fig.10 It can be seen that the carbon nanofibers prepared in the present application by introducing liquid melamine phosphate into the PAN / DMF precursor spinning solution and the lignin / PAN / DMF precursor spinning solution have a smooth surface and a uniform diameter distribution, while the carbon nanofibers prepared using powdered melamine powder have agglomerations inside and an uneven diameter distribution. Figure 7 The internal structure of the carbon nanofibers prepared without adding liquid melamine phosphate is sparse. This application introduces liquid melamine phosphate, which synergistically enhances the density of the hydrophilic carbon nanofibers with polyacrylonitrile and lignin during the calcination process, which can improve the density inside the carbon nanofibers, reduce the internal agglomeration of the fibers, and thus improve the hydrophilic properties.

[0072] The water contact test was measured using an OCA15EC contact angle analyzer (Data-physics, Germany). Water droplets of the same size were dropped on the fiber surface to observe the angle and diffusion rate formed by the water droplets on the fiber surface. Example 1, Example 3 and Comparative Example 3 PAN / melamine hydrophilic carbon nanofibers prepared using liquid melamine phosphate such as Figure 11-13 As shown in the figure, the hydrophilicity of the fiber is characterized by the diffusion rate of water droplets on the fiber felt surface. The water droplets on the fiber surface of PAN / melamine hydrophilic carbon nanofibers prepared by carbonizing at 400 degrees for 1 hour in a nitrogen atmosphere were completely absorbed within 11ms, and the water droplets on the fiber surface obtained by carbonizing at 800 degrees were completely diffused within 63ms. However, the degree of graphitization of the fiber obtained by carbonizing at 1200 degrees increased, the hydrophilicity decreased, and the surface water was completely diffused within 71s.

[0073] The water contact angle test was performed on the lignin / PAN / melamine hydrophilic carbon nanofibers prepared with liquid melamine phosphate in Example 2, Example 4 and Comparative Example 4. Figures 14 to 16 As shown in the figure, it can be seen that the contact angles of carbon nanofibers prepared at 400℃ and 800℃ are more hydrophilic. When the temperature rises to 1200℃, the hydrophilicity decreases due to the increase of graphitization. Figure 14-16 As shown in the figure, the hydrophilicity of the fiber is characterized by the diffusion rate of water droplets on the surface of the fiber felt. The water droplets on the surface of the lignin / PAN / melamine hydrophilic carbon nanofibers prepared by liquid melamine phosphate were carbonized at 400 degrees in a nitrogen atmosphere for 1 hour. They were completely absorbed within 16ms, and the water droplets on the surface of the fiber carbonized at 800 degrees were completely diffused within 82ms. However, the degree of graphitization of the fiber obtained after carbonization at 1200 degrees increased, and the hydrophilicity decreased. The water on the fiber surface was completely diffused after 71s.

[0074] The water absorption test was carried out on Example 1 and Example 2. Figure 5 , Figure 6 As shown, water is dyed with a fluorescent agent to absorb water. It can be seen that the hydrophilicity of the fiber after the liquid melamine phosphate hydrophilic modification is greatly improved, and the rapid anti-gravity transmission of water can be achieved. Water is dropped on the PAN-based carbon nanofiber prepared in Comparative Example 1. Figure 8 As shown, it can be seen that the carbon nanofibers prepared without adding liquid melamine phosphate are highly hydrophobic and hardly absorb water. It also shows that adding liquid melamine phosphate can improve the water absorption of carbon nanofibers.

[0075] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.

Claims

1. A hydrophilic carbon fiber spinning solution, characterized in that: The hydrophilic carbon fiber spinning stock solution is prepared by adding a precursor spinning raw material to NN-dimethylformamide, and then introducing liquid melamine phosphate for modification. The mass ratio of the precursor spinning raw material, liquid melamine phosphate, and NN-dimethylformamide is 10-20:3-6:90-110. The preparation method of the liquid melamine phosphate is as follows: adding a modifying auxiliary phosphoric acid to a liquid melamine resin, stirring with a magnetic stirrer for 2 hours to mix evenly to prepare the liquid melamine phosphate. The mass ratio of the liquid melamine resin to the modifying auxiliary phosphoric acid is 1:3-6.

2. The hydrophilic carbon fiber spinning solution according to claim 1, characterized in that: The precursor spinning raw materials are one or two of polyacrylonitrile and lignin.

3. The air-spinning method of the hydrophilic carbon fiber spinning solution according to claim 1 or 2, characterized in that: The steps include: (1) transferring the hydrophilic carbon fiber spinning stock solution into a syringe pump to perform solution spray spinning to obtain precursor fiber cotton; (2) After the precursor fiber cotton is dried, it is carbonized at 400-800° C. in a nitrogen environment to obtain hydrophilic carbon nanofibers.

4. The air spinning method according to claim 3, characterized in that: During the solution jet spinning process, the spinning parameters are set as follows: the spinning air pressure is 0.2-0.4 MPa, the spinning flow rate is stabilized at 10-30 mL / h, and the spinning distance is 30 cm.

5. The air spinning method according to claim 3, characterized in that: The drying is specifically as follows: placing the precursor fiber in a drying oven at 50 to 60° C. and performing a drying treatment for 10 to 20 hours.

6. The air spinning method according to claim 3, characterized in that: After the precursor fiber cotton is dried, it is placed in a muffle furnace for pre-oxidation at 220-260° C. and then carbonized.

7. The air spinning method according to claim 3, characterized in that: The carbonization heating rate is 4-8°C / min, and the carbonization time is 0.5-2h.

8. A method for preparing hydrophilic carbon nanofibers, characterized in that: The hydrophilic carbon fiber spinning stock solution described in any one of claims 1 or 2 is transferred into an injection pump for solution spray spinning to obtain a precursor fiber cotton. After the precursor fiber cotton is dried, it is pre-oxidized at 220 to 260° C. and then carbonized at 400 to 800° C. in a nitrogen environment to obtain hydrophilic carbon nanofibers.

9. A hydrophilic carbon nanofiber prepared according to the method of claim 8.

Citation Information

Patent Citations

  • Toughening material of composite material and preparation method toughening material

    CN102505355A

  • Preparation method for biomass-based carbon nanofiber

    CN111197187A

  • Lignin / polyacrylonitrile-containing dopes, fibers, and methods of making same

    US20120003471A1

  • Porous carbon nanofiber material having parallel pore channel structures and preparation method therefor

    WO2024152668A1